2022
DOI: 10.3390/ijerph192114589
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Game Analysis of Government and Residents’ Participation in Waste Separation Based on Cumulative Prospect Theory

Abstract: Government and residents’ participation in waste separation is a complex non-cooperative game process, and the evolutionary game can explain the behavior of participating subjects well. Considering that the traditional evolutionary game cannot satisfactorily explain the irrational psychology and risk preference factors of the participating issues, this study combines the prospect theory and evolutionary game, uses the prospect value function to supplement and improve the parameters of the evolutionary game pay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The result is similar with Chen and Gao [ 59 ] who used multi-agent-based simulation to investigate the learning measures of residents' waste separation behavior. This finding also echoes the study of Zhang et al [ 58 ] who found that higher waste separation benefits and lower costs can increase residents' participation rates of waste separation. This indicated that it is necessary not only to reduce the cost of sorting waste and increase the penalty for non-classification but also to reduce the management costs of property service companies, as well as to increase subsidies for them.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The result is similar with Chen and Gao [ 59 ] who used multi-agent-based simulation to investigate the learning measures of residents' waste separation behavior. This finding also echoes the study of Zhang et al [ 58 ] who found that higher waste separation benefits and lower costs can increase residents' participation rates of waste separation. This indicated that it is necessary not only to reduce the cost of sorting waste and increase the penalty for non-classification but also to reduce the management costs of property service companies, as well as to increase subsidies for them.…”
Section: Discussionsupporting
confidence: 88%
“…Wu et al [ 17 ] established the evolutionary game model involving the government and residents in municipal household waste separation. Based on the prospect theory and evolutionary game, Zhang et al [ 58 ] investigated the behavior change process of government and residents to understand how to optimize the benefits of waste separation for stakeholders. Chen and Gao [ 59 ] analyzed the behavioral strategies of residents, waste disposal companies, and the government in waste separation and recycling using evolutionary games and studied the stability of the evolutionary system through multi-agent-based simulation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of waste resource utilization, Wang et al [43] integrated prospect theory into the trilateral evolutionary game theory to analyse the utilization process of construction waste resources by local governments, construction companies, and the public. Zhang et al [44] combined prospect theory and evolutionary games and found that residents' participation benefits are higher, participation costs and opportunity costs are lower, and reasonable direct benefit distribution coefficients can help increase the participation rate in waste classification. In terms of carbon emission reduction, Zhang et al [45] used the two-party evolutionary game model of prospect theory to study the interactive relationship between local governments and port enterprises in the context of green port construction.…”
Section: Research On Prospect Theorymentioning
confidence: 99%